Autophagy in T Cell Function and Aging - Macian, Fernando (Frontiers in Cell and Developmental Biology, 2019)
Dysregulation of autophagy with age has been identified as a central mechanism of aging affecting many cells and tissues. T cells do also show decreased activity with age of different autophagic pathways. Here, we will review the current knowledge of the different functions that autophagy has in the regulation of T cell homeostasis, differentiation and function and explore how the age-associated decreased in autophagy activity may contribute to the altered T cell responses that characterize T cell immunosenescence.